Voltaglue bioadhesives energized with interdigitated 3D‐graphene electrodes - Singh, Manisha (2020)
Soft tissue fixation of implant and bioelectrodes relies on mechanical means (e.g., sutures, staples, and screws), with associated complications of tissue perforation, scarring, and interfacial stress concentrations. Adhesive bioelectrodes address these shortcomings with voltage cured carbene-based bioadhesives, locally energized through graphene interdigitated electrodes. Electrorheometry and adhesion structure activity relationships are explored with respect to voltage and electrolyte on bioelectrodes synthesized from graphene 3D-printed onto resorbable polyester substrates. Adhesive leachates effects on in vitro metabolism and human-derived platelet-rich plasma response serves to qualitatively assess biological response. The voltage activated bioadhesives are found to have gelation times of 60 s or less with maximum shear storage modulus (G') of 3 kPa. Shear modulus mimics reported values for human soft tissues (0.1-10 kPa). The maximum adhesion strength achieved for the ≈50 mg bioelectrode films is 170 g cm-2 (17 kPa), which exceeds the force required for tethering of electrodes on dynamic soft tissues. The method provides the groundwork for implantable bio/electrodes that may be permanently incorporated into soft tissues, vis-à-vis graphene backscattering wireless electronics since all components are bioresorbable.